Examining the English language policy for ethnic minority students in a Chinese university: a language ideology and language regime perspective. Issue 3 (1st October 2016) - Han, Yawen; De Costa, Peter I.; Cui, Yaqiong
ABSTRACT: We focus on the learning of English in a Chinese university in Jiangsu and the university's preferential language policy, which allowed Uyghur minority students from Xinjiang to be enrolled despite their lower scores in the entrance examination. Guided by the constructs of language ideologies [Kroskrity, P. V. (2000). Regimes of language: Ideologies, politics, identities . Santa Fe, NM: School of American Research Press] and language regimes [Sonntag, S. K., & Cardinal, L. (2015). Introduction. In L. Cardinal & S. K. Sonntag (Eds.), State traditions and language regimes (pp. 3–26). Montreal: McGill-Queen's University Press], we adopted an ethnographic approach [McCarty, T. L. (2015). Ethnography in language planning and policy research. In F. M. Hult & D. C. Johnson (Eds.), Research methods in language policy and planning: A practical guide (pp. 81–93). Malden, MA: Wiley Blackwell] to investigate how Uyghur students viewed their English learning and how the university responded to macro-level national language planning decisions to foster social harmony. Our findings revealed that the minority students were marginalized in their study of English and disadvantaged compared to Han students. Consequently, we argue for a consideration of the impact of power inequalities in relation to English language learning. Such a critical perspective entails (1) acknowledging the disadvantaged position from which these minority students began their formal education because English was a third language for them [Yang, J. (2005). English as a third language among China's ethnic minorities. International Journal of Bilingual Education and Bilingualism, 8 (6), 552–567] and (2) recognizing that access to English education is not equitable because students who attend schools in economically developed provinces such as Jiangsu are more likely to get a better education in English than those from a less developed province such as Xinjiang.